Aluminum improves the growth and quality of yerba mate (Ilex paraguariensis, Aquifoliaceae) clonal seedlings (Research, Society and Development, 2020)
In this study, doses of aluminum (Al3+) in the rooting substrate were evaluated for growth, nutrition and quality of yerba mate clonal seedlings. Different levels of Al3+ were incorporated into the substrate in the form of aluminum sulphate (0.00; 2.25; 4.50; 9.00 and 18.00 g dm-³). At 90, 150, 215 and 300 days after planting the cuttings (DAE), morphological attributes and seedling SPAD index were evaluated. At 90 and 300 DAE, the consistency of the clod (root ball), fresh and dry matter of roots, stem, and leaves were evaluated. Based on these attributes, the Dickson Quality Index (IQD) was calculated, and the leaves were used to determine the leaf area and the concentrations of macro and micronutrients and Al. The growth of the seedlings was influenced by Al3+ supply and the time of evaluation. The maximum values ​​of neck diameter, height, number of leaves, and dry matter of leaves and leaf area at 300 DAE were observed with the dose of 9.00 g dm-³ of aluminum sulfate (SA). The leaf concentration of Al was higher in the dose 9.00 g dm-3 of SA, and the concentrations of Ca and K were reduced due to the application of SA doses. The quality (IQD) was positively affected by Al3+ supply, increasing up to the application of 9.00 g dm-³ of SA. It was concluded that the dose of 9.00 g dm-³ of aluminum sulfate in the substrate provided the best results in the production of clonal seedlings of yerba mate.